Understanding Campus Culture and Student Coping Strategies for Mental Health Issues in Five Canadian Colleges and Universities - Giamos, Dimitris; Lee, Alex Young Soo; Suleiman, Amanda; Stuart, Heather; Chen, Shu-Ping (Canadian Journal of Higher Education, 2017)
This study aimed to better understand campus mental health culture and student mental health coping strategies, and to identify the mental health needs of students as well as gaps in mental health services within postsecondary education. A videovoice method was used to identify and document health-related issues and advocate for change. Forty-one interviews were conducted with campus stakeholders at five universities. Five themes involving mental health emerged from the campus interviews: the stigma of mental illness; campus culture related to mental health; mental health services available and barriers to mental health services on campus; accommodations for students’ mental health needs; and student mental health coping strategies. A documentary was developed to advocate for better mental health. We conclude that although Canadian campuses are raising awareness about mental health issues, there is not enough mental health infrastructure support on campuses; in particular, accessibility to campus mental health resources needs improvement.